Correlation between low FAT1 expression and early affected muscle in facioscapulohumeral muscular dystrophy. Issue 3 (3rd July 2015) - Mariot, Virginie; Roche, Stephane; Hourdé, Christophe; Portilho, Debora; Sacconi, Sabrina; Puppo, Francesca; Duguez, Stephanie; Rameau, Philippe; Caruso, Nathalie; Delezoide, Anne‐Lise; Desnuelle, Claude; Bessières, Bettina; et al.
<x xml:space="preserve">Abstract</x> Objective Facioscapulohumeral muscular dystrophy (FSHD) is linked to either contraction of D4Z4 repeats on chromosome 4 or to mutations in the SMCHD1 gene, both of which result in the aberrant expression of the transcription factor DUX4. However, it is still difficult to correlate these genotypes with the phenotypes observed in patients. Because we have recently shown that mice with disrupted Fat1 functions exhibit FSHD‐like phenotypes, we have investigated the expression of the human FAT1 gene in FSHD. Methods We first analyzed FAT1 expression in FSHD adult muscles and determined whether FAT1 expression was driven by DUX4. We next determined FAT1 expression levels in 64 muscles isolated from 16 control fetuses. These data were further complemented with analysis of Fat1 expression in developing mouse embryos. Results We demonstrated that FAT1 expression is independent of DUX4. Moreover, we observed that (1) in control fetal human biopsies or in developing mouse embryos, FAT1 is expressed at lower levels in muscles that are affected at early stages of FSHD progression than in muscles that are affected later or are nonaffected; and (2) in adult muscle biopsies, FAT1 expression is lower in FSHD muscles compared to control muscles. Interpretation We propose a revised model for FSHD in which FAT1 levels might play a role in determining which muscles will exhibit early and late disease onset, whereas DUX4 may worsen the muscle phenotype. Ann Neurol 2015;78:387–400